2018
DOI: 10.3390/ijgi7070281
|View full text |Cite
|
Sign up to set email alerts
|

Using Eye Tracking to Evaluate the Usability of Flow Maps

Abstract: Flow maps allow users to perceive not only the location where interactions take place, but also the direction and volume of events. Previous studies have proposed numerous methods to produce flow maps. However, how to evaluate the usability of flow maps has not been well documented. In this study, we combined eye-tracking and questionnaire methods to evaluate the usability of flow maps through comparisons between (a) straight lines and curves and (b) line thicknesses and color gradients. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Visual behavior can be retrieved from the analysis of locations of PORs, since, according to the 'mind-eye hypothesis' [52], people tend to look at things they are thinking about. Eye-tracking has been applied to various GIS empirical studies: to evaluate enhanced imagery evaluation [53], size and color of text on maps [54], comparison of 3D maps and 2D maps [55], features of flow maps [18], etc. The combination of eye-tracking and other methods has been used in recent studies with confirmed effectiveness [37,[56][57][58].…”
Section: Methods Of Gaining Insight Into Map-reading and Analysismentioning
confidence: 99%
“…Visual behavior can be retrieved from the analysis of locations of PORs, since, according to the 'mind-eye hypothesis' [52], people tend to look at things they are thinking about. Eye-tracking has been applied to various GIS empirical studies: to evaluate enhanced imagery evaluation [53], size and color of text on maps [54], comparison of 3D maps and 2D maps [55], features of flow maps [18], etc. The combination of eye-tracking and other methods has been used in recent studies with confirmed effectiveness [37,[56][57][58].…”
Section: Methods Of Gaining Insight Into Map-reading and Analysismentioning
confidence: 99%
“…The use of these metrics is essential. Fixations allow 1 exact determination of the user's focused attention, and together with saccades are elementary components of eye movement [62,63]. Fixations are responsible for the processing of visual information.…”
Section: Eye Movement Metricsmentioning
confidence: 99%
“…The results showed that improving visual hierarchy affected viewing behavior and response time. Studies of similar design were conducted with other types of materials, for example 2D and 3D pie charts [12], cartograms [13], maps of spatial accessibility [14], graduated symbols in relation to spatial distance between them [15] or flow maps [16]. All of these provided empirical evidence valuable for formulating the optimal solution for a particular map type, and guidance on how to refine a selected map type.…”
Section: Informationally Equivalent Visualizationsmentioning
confidence: 99%